Developing PHYCOM (Physics Comics) on Newton’s Law Material for 10th Grade High School Students - Baifeto, Ekri Pranata Ferdinand; Samsudin, Achmad; Efendi, Ridwan; Athiyyah, Royhanun (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
This research aims to develop high school physics teaching materials in the form of comics. This research method is a research and development (R&D) method. The steps in this method are Analysis-Design-Development-Implementation-Evaluation (ADDIE). A validation test was carried out using a questionnaire to obtain valid Physics Comics (PHYCOM) teaching materials. This feasibility test was carried out by three validators consisting of 1 high school physics teacher, two lecturers, and six 10th-grade high school students. Comics are said to be valid and feasible to use because they meet the validity percentage at a value of 61% - 100% (valid criteria and very valid). Based on the results of the feasibility test of the three validators, it was found that PHYCOM's teaching materials were very valid and feasible to use, with a percentage of 87.50%. The validation results from six students showed that PHYCOM was a very valid teaching material with a validity percentage of 91.18%. The results of this validation indicate that PHYCOM is valid and suitable to be used as teaching materials for 10th high school students. The advantage of PHYCOM teaching materials is that they are communicative and contain illustrative images so that they are easy to visualize. In addition, PHYCOM teaching materials can be used by students as independent study materials.